(untitled) (Bangladesh Journal of Microbiology, 2020)
Hepatitis E virus (HEV) infection is a significant public health issue in many developing countries, causing waterborne outbreaks as well as sporadic hepatitis. We report here an outbreak of HEV genotype 1f infection during Apr-May 2018 among persons living at Halisohor, a low land of southern part of Chottogram District of Bangladesh. A total of 933 patients were admitted in Combined Military Hospital (CMH) Chottogram with symptoms of acute hepatitis. Among them 550 patients were tested by ELISA for HEV specific IgM and all were positive. Genotyping, sequencing and phylogenetic analysis based on ORF 2 region revealed that the outbreak was caused by genotype 1f and the strains were closely related to the previously reported HEV strains that caused outbreak in Bangladesh in 2010. The current outbreak was most likely linked with water supply as fecal contamination in water was evident and could be prevented by ensuring access to safe drinking water. Bangladesh J Microbiol, Volume 37 Number 1 June 2020, pp 35-37